Youth risk profiles and their prediction of distal cannabis and tobacco co-use in the Population Assessment of Tobacco Health (PATH). Issue 1 (1st December 2022) - Smith, Crystal Lederhos; Rhoades Cooper, Brittany; Miguel, Andre; Roll, John; Hill, Laura; Cleveland, Michael; McPherson, Sterling
Abstract: Background: Co-use of cannabis and tobacco is common and increases negative behavioral, physical and mental health consequences. This study aimed to describe latent profiles of youth internalizing and externalizing problems, sensation seeking, and family environment in the US and their relationships with substance co-use. Methods: Data come from the Population Assessment of Tobacco Health (PATH). Using latent profile analysis with a distal outcome, we conducted a secondary data analysis examining relationships between latent profiles and the distal outcome of cannabis/tobacco use and co-use one year later. Participants were a nationally representative sample of youth ages 12–17 ( N = 13, 651). Results: We identified five youth subgroups: (1;11%) Family Risk, (2;32%) Family Protection with Very Low Internalizing, (3;21%) Family Protection with High Youth Risk, (4;24%) Family Protection with Moderate Youth Risk, (5;12%) Family Risk with High Youth Risk . Relationships between group membership and tobacco/cannabis outcomes, one year later, indicated that the least likely tobacco/cannabis users were the Family Protection with Very Low Internalizing class (no lifetime use probability (PR) =0.86, standard error (SE) =0.007; no 30-day use PR = 0.96, SE = 0.004). In contrast, the Family Risk with High Youth Risk class had the highest probability of both co-use (lifetime co-use PR = 0.33; SE = 0.014; 30-day co-use PR = 0.10; SE = 0.010) and single substance use (probability of lifetime single substance use PR = 0.30; SE = 0.013; 30-day single substance use PR = 0.24; SE = 0.014). Conclusions: A "protective but reactive" risk buffering pattern effect of family factors on youth factors was observed in that the lowest rates of co-use were observed in the three classes with family protection. These findings highlight the need for interventions addressing multiple domains and focusing on youth and family risk factors.